2022
DOI: 10.1021/acs.joc.1c02890
|View full text |Cite
|
Sign up to set email alerts
|

NaN(SiMe3)2/CsTFA Copromoted Aminobenzylation/Cyclization of 2-Isocyanobenzaldehydes with Toluene Derivatives or Benzyl Compounds: One-Pot Access to Dihydroquinazolines and Quinazolines

Abstract: A NaN­(SiMe3)2/CsTFA copromoted aminobenzylation/cyclization reaction of 2-isocyanobenzaldehydes with toluene derivatives or benzyl compounds has been developed. The reaction works with a broad range of toluene derivatives and benzyl compounds, and provides a simple and efficient strategy for the synthesis of 4-benzyl-substitued dihydroquinazoline and quinazoline derivatives from easily available acyclic starting materials in a single step. Further applications, including synthesis of quinazoline, dihydroindol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…On the basis of our experimental results and the literature, , a possible mechanism is proposed (Scheme ). The reaction commences with oxidation of 1a to give intermediate A .…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…On the basis of our experimental results and the literature, , a possible mechanism is proposed (Scheme ). The reaction commences with oxidation of 1a to give intermediate A .…”
Section: Resultsmentioning
confidence: 74%
“…The reaction commences with oxidation of 1a to give intermediate A . Next was the benzylic C–H bond activation of intermediate A by the synergistic action of LiN­(SiMe 3 ) 2 and KO t Bu, affording a nucleophilic benzyl-metal species B , which quickly experiences nitrile addition to form metalated imine intermediate C . The subsequent intramolecular imine–carbonyl nucleophilic addition reaction gives intermediate D. The following protonation of intermediate D and dehydration/aromatization takes place to form isoquinolone 3a . Alternatively, a simultaneous nitrogen-exchange step with the assistance of HN­(SiMe 3 ) 2 , LiN­(SiMe 3 ) 2 , and KO t Bu promotes the formation of intermediate C′ , which further undergoes a nucleophilic addition reaction to afford intermediate D′ .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With continuous effort towards the synthesis of decorated heterocycles by the chemists, in the successive year Zhao group reported the synthesis of dihydroquinazoline 61 and quinazoline derivatives 62 using the aminobenzylation strategy (Scheme 29). [82] Here they took the challenging task of activating benzylic CÀ H bonds and further cyclizing it with isocyanide in obtaining dihydroquinazolines and quinazolines with the help of NaN(SiMe 3 ) 2 and CsTFA combination. In this developed condition, they observed that the usage of solid NaN(SiMe 3 ) 2 in toluene gave lower yield whereas NaN(SiMe 3 ) 2 2 M in THF delivered the better yield.…”
Section: Annulationmentioning
confidence: 99%
“…It should be pointed out that we used relatively mild bases [MN­(SiMe 3 ) 2 (M = Li, Na)/Cs + ] [p K a ≈ 26 for HN­(SiMe 3 ) 2 in THF], and the corresponding deprotonations of weakly acidic C­(sp) 3 –H bonds (p K a ≈ 43) were facilitated by the proposed alkali cation−π interactions. More recently, our NaN­(SiMe 3 ) 2 /CsTFA system was successfully applied to tandem synthesis of dihydroquinazolines and quinazolines by Zhao and co-workers, which further demonstrated the utility of the deprotonative system in synthesis of bioactive compounds …”
Section: Introductionmentioning
confidence: 99%